FINITE ELEMENT ANALYSIS AND EXPERIMENTAL STUDY ON THE STRENGTH OF A HEAVY LOAD TRANSMISSION END CAP - YAO Yao; YU WeiYi; ZHAO LiHui; MA Jiong; FENG JinZhi; ZHENG SongLin (Jixie qiangdu)
The current structural optimization steps are the first finite element modeling,followed by optimization analysis.In order to improve the accuracy of the analysis and ensure the rationality of the structural optimization results,the finite element model needs to be verified. In this paper,finite element analysis is carried out for the left end cap of a heavy load transmission box in China. According to the finite element analysis results,the measured points are selected and the loaded is measured. The finite element model is verified by the measured load spectrum of the end cap. It is found that the dynamic load generated by the gear meshing is about 1. 1 to 2. 5 times of the static load,but the pre-finite element analysis does not take into account the effect of dynamic loading,which can lead to early failure of the end cap during service. Finally,the boundary condition of the load is modified by indirectly obtained dynamic load factor,which makes the modified finite element model more accurate. Which provides an accurate model for the later optimization design.